Biportal Endoscopic Spine Surgery for Single Lumbar Disc Herniation or Lumbar Stenosis: Comparison between right and left side approach of right-handed surgeon - Foocharoen, Thanit (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Aim of the study was to compare the outcomes of the surgical treatment between right sided biportal endoscopic spine surgery (R-BESS) and the left sided biportal endoscopic spine surgery (L-BESS) approach for single-level lumbar disc herniation (LDH) or lumbar spinal stenosis (LSS) of right-handed surgeon. Methods: Retrospective cohort study was conducted in adult patients with single LDH or LSS who underwent biportal endoscopic lumbar discectomy or lumbar stenosis decompression by right-handed spine surgeon between December 2018 and May 2020. The surgical side approaches were chosen according to symptomatic side and the finding from magnetic resonance imaging. Perioperative and post-operative outcomes were evaluated comparison between L-BESS and R-BESS. Results: A total of 51 cases were enrolled, of which female to male ratio was 30:21 Mean age was 40.2±10.8 years. Thirty-one cases underwent L-BESS with the ratio for L-BESS and R-BESS was 1.5:1. L4/5 level was the most common surgical level in both L-BESS and R-BESS approach. The mean operative time (OT), mean estimated blood loss, Oswestry Disability Index (ODI) before and after surgery, back pain evaluated by visual analogue score (VAS) before and after surgery, MacNab criteria for patient satisfactory outcomes, hospital stay, hospital costs and immediate postoperative complication were not significant difference between L-BESS and R-BESS with p=0.77, 0.22, 0.52, 0.08, 0.18, 0.67, 0.82, 0.59, 0.27, and 0.30, respectively. Conclusions: BESS for single LDH or LSS had comparable perioperative and postoperative outcomes between right and left sided approach.